2017
DOI: 10.1103/physrevphyseducres.13.020104
|View full text |Cite
|
Sign up to set email alerts
|

Doing science by waving hands: Talk, symbiotic gesture, and interaction with digital content as resources in student inquiry

Abstract: In this paper, we investigate some of the ways in which students, when given the opportunity and an appropriate learning environment, spontaneously engage in collaborative inquiry. We studied small groups of high school students interacting around and with an interactive whiteboard equipped with Algodoo software, as they investigated orbital motion. Using multimodal discourse analysis, we found that in their discussions the students relied heavily on nonverbal meaning-making resources, most notably hand gestur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
(69 reference statements)
1
18
0
2
Order By: Relevance
“…However, research has shown that, in addition to resources such as mathematical formalisms and spoken language, physics students also often recruit other resources such as gestures and manipulations of their surroundings to make meaning. For example, Gregorcic et al [12] provide an analysis that shows how small groups of students described patterns, proposed experiments, and predicted outcomes in a sciencelike manner, all while using "hand waving," manipulations of a large touch-screen, and informal vocabulary. The study provides an example of students producing qualitative descriptions of orbital motion akin to Kepler's laws, showing that nondisciplinary meaning-making resources can manifest conceptual and procedural ideas that are worthwhile from a physics disciplinary perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research has shown that, in addition to resources such as mathematical formalisms and spoken language, physics students also often recruit other resources such as gestures and manipulations of their surroundings to make meaning. For example, Gregorcic et al [12] provide an analysis that shows how small groups of students described patterns, proposed experiments, and predicted outcomes in a sciencelike manner, all while using "hand waving," manipulations of a large touch-screen, and informal vocabulary. The study provides an example of students producing qualitative descriptions of orbital motion akin to Kepler's laws, showing that nondisciplinary meaning-making resources can manifest conceptual and procedural ideas that are worthwhile from a physics disciplinary perspective.…”
Section: Introductionmentioning
confidence: 99%
“…However, while Ref. [12] illustrates how students can arrive at descriptions of orbital motion through spontaneous, informal means, it remains relatively unexplored how students might recruit a similar interplay of meaning-making resources to develop explanations of similar phenomena. To address this unexplored aspect, our investigation presented in this paper builds on Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of gestures in communicating disciplinary knowledge in physics and astronomy has recently been recognized by others, for example, Refs [66]. and[67].…”
mentioning
confidence: 99%
“…Eles abordam aulas de Química Orgânica do Ensino Superior Chue, Lee, & Tan, 2015), professores de Química do Ensino Médio (Danielsson, 2016;Abels, 2016), professores de Química em formação inicial (Giordan, Silva-Neto, & Aizawa, 2015), professores de Ciências do Ensino Médio (Wilson, Boatright, & Landon-Hays, 2014), professores de Ciências do Ensino Fundamental (Piccinini & Martins, 2005;Sessa & Trivelato, 2017;Oliveira et al, 2014) e até mesmo um tutor virtual (desenho animado) que usava gestos ao comunicar as atividades on-line (Martins, Demorais, Schaab, & Jaques, 2016). Outros trabalhos analisam os gestos em estudantes do Ensino Fundamental (Kapon, 2017;Ünsal, Jakobson, Wickman, & Molander, 2018), de Ensino Médio (Gregorcic, Planinsic, & Etkina, 2017) e envolvendo estudantes do Ensino Fundamental e universitários (Ianì, Cutica, & Bucciarelli, 2017). Esses são alguns exemplos de trabalhos envolvendo gestos, que mostram uma intensa e promissora contribuição na comunicação, no ensino e na aprendizagem.…”
Section: B) a Multimodalidade Na Comunicação E Na Produção De Signifiunclassified